On I-Deferred Statistical Convergence - Sengul, Hacer; Et, Mikail; Isik, Mahmut (Amer Inst Physics, 2019)
The idea of I-convergence of real sequences was introduced by Kostyrko et al. [Kostyrko, P., Salat, T and Wilczynski, W I-convergence, Real Anal. Exchange 26(2) (2000/2001), 669-686] and also independently by Nuray and Ruckle [Nuray, F. and Ruckle, W H. Generalized statistical convergence and convergence free spaces. J. Math. Anal. Appl. 245(2) (2000), 513-527]. In this paper we introduce I-deferred statistical convergence and strong I-deferred Cesaro convergence and investigate between their relationship.
International Conference of Mathematical Sciences (ICMS) -- JUL 31-AUG 06, 2018 -- Maltepe Univ, Istanbul, TURKEY
Keywords: Sequences; series; summability; functional analysis